(untitled) (Veterinary Science, 2017)
Leptospirosis is a zoonotic disease of world significance affecting many animal species, thus becoming an important issue in public health. The infection is caused by different antigenic serotypes of Leptospira interrogans. Several cases in canines were detected at the Medical Clinic Department of Small Animals at the Faculty of VeterinarySciences (UNLPam). This report consists of an exploratory study to detemime the prevalence of human and canine Leptospirosis in the city of general Pico and zone of influence which at present is unknown. 151 human and 195 canine serum samples were already obtained. The former were collected from risky areas (cold-storage plant, urban recycled waste plant and army regiment) while the latter were got from dogs treated at the above-metioned departament besides those pertaining to the town hall’s kennel. The seropositive determination is carried out by means or Martin’s and Petit’s microaglutination techique with live antigens and using 8 serovars (Leptopiras canicola, pomona, icterohemorragiae, castellonis, grippo-thyphosa, pyrágenes, tarassovi, woljJi). Although the analysis on the total collected amples has not been yet finished, the preliminary results make evident 10 and 52 positive cases (with detection of serovars) in humans and dogs respectively